Effects of kinesiology taping timing on recovery in the lower limbs - Tang, Chia-Yu; Huang, Ying-Che; Hsu, Fu-Shun; Yu, Chia-Hsien; Lai, Chang-Chi; Fu, Szu-Kai (Frontiers in Physiology, 2025)
BackgroundKinesiology taping (KT) is widely used to support muscle function and recovery, but its optimal application timing remains unclear. While some suggest pre-exercise KT provides protective benefits, others propose post-exercise KT aids recovery. Eccentric contractions often lead to eccentric exercise-induced muscle damage (EIMD), causing strength loss, soreness, and reduced range of motion. Whether KT timing influences its effectiveness in mitigating or accelerating EIMD recovery requires further investigation.PurposeThis study examined whether KT, applied before (KT-pre) or after (KT-post) eccentric exercise of the knee extensors, could mitigate or hasten recovery from EIMD in the lower limbs.Methods12 healthy adult males (22.0 ± 1.7 years) participated in a repeated-measures crossover study under three conditions: KT-pre, KT-post, and a no-taping control (CON). Participants performed 72 eccentric contractions of the knee extensors on the non-dominant leg using an isokinetic dynamometer. Outcome measures included maximal voluntary isometric contraction (MVIC) normalized to body weight, rate of force development (RFD) in the 0–200 ms interval, neuromuscular efficiency (NME, defined as the ratio of peak torque to integrated electromyography), active ROM of knee flexion (measured via goniometry), and subjective muscle soreness (100-mm visual analogue scale). Assessments were conducted at baseline and at 0-, 24-, and 48-h post-exercise.ResultsWhen expressed as a percentage of baseline, both peak torque and RFD in the 0–200 ms interval declined significantly at 0- and 24-h post-exercise (p < 0.05) in all groups, with no significant intergroup differences. The iEMG parameter remained unchanged. NME declined significantly at 0 h (p < 0.05) in all conditions; however, at 24 h, the KT-pre group exhibited significantly higher NME than the control (79.3% ± 12.8% vs. 94.4% ± 17.4%, p = 0.0052). Active ROM decreased and subjective muscle soreness increased significantly at 0 and 24 h (p < 0.05) across all groups, with no significant intergroup differences.ConclusionAlthough KT-pre demonstrated a short-term protective effect immediately after eccentric exercise, neither pre- nor post-exercise taping significantly mitigated muscle damage or enhanced recovery. Further research is needed to clarify KT’s long-term benefits and its effects on EIMD in other muscle groups.